Evaluation of an online motivational interviewing training program for rehabilitation professionals: A pilot study - Schechter, Nicole; Butt, Lester; Jacocks, Connie; Staguhn, Elena; Castillo, Renan; Wegener, Stephen T (Clinical rehabilitation, 2021)
To investigate the feasibility and effectiveness of an online motivational interviewing training program for rehabilitation professionals. Pre-post design with two groups. Private rehabilitation hospital and an academic medical center. Group 1 included 19 motivational interviewing-experienced rehabilitation professionals. Group 2 included 25 motivational interviewing-naïve rehabilitation professionals. Group 1 was exposed to an online motivational training program and Group 2 was exposed to an online motivational training program and a live booster session. Motivational interviewing communication skills were measured with an adapted Helpful Responses Questionnaire. Knowledge and attitudes were measured with an adapted Motivational Interviewing Knowledge and Attitudes Test. Confidence, importance, and feasibility for implementing motivational interviewing were measured using the Motivational Interviewing Rulers. Group 1 showed improvement in communication skills (2.6/5-3.3/5; < 0.05) and confidence (6.0/01-7.4/10; < 0.01) after online training. Improvements seen in skills and confidence were maintained at three months. Group 2 showed improvement in skills (2.1/5-3.3/5; < 0.001), knowledge (7.7/10-8.5/10; < 0.01), confidence (6.4/10-7.5/10; < 0.01), and importance (8.3/10-8.9/10; < 0.05) after online training. At three-months post-booster, improvements in communication skills and knowledge were maintained. Online training can be a cost and time effective approach to improve rehabilitation professionals' skills in motivational interviewing. Follow-up training activities are needed to maintain the level of knowledge and skill improvement.